Accurate and precise quantification of Cu, Zn-SOD in human red blood cells using species-specific double and triple IDMS. Issue 9 (7th April 2016) - Gleitzmann, Julia; Raab, Andrea; Schulze, Dirk; Wätzig, Hermann; Feldmann, Jörg; Swart, Claudia
Abstract : Species-specific double and triple isotope dilution mass spectrometry (IDMS) was applied for the precise quantification of Cu, Zn-SOD in human erythrocytes. Abstract : Cu, Zn-superoxide dismutase (SOD1) is a protein involved in the antioxidant defense system of the body responsible for the dismutation of the superoxide anion. It contains two Cu and two Zn ions per molecule. As this protein is also involved in several diseases it is used in clinical diagnostics as a biomarker, which requires the accurate and reliable determination of SOD1. Therefore, a candidate reference measurement procedure for the quantification of this protein in human erythrocytes was developed using species-specific isotope dilution mass spectrometry (IDMS), a method giving results traceable to the International System of Units (SI). The measurement procedure was validated with regard to a metrological point of view. Commercially available SOD1 was thoroughly characterized to be used as a pure protein calibration standard in IDMS approaches. Furthermore, 65 Cu and 67 Zn labeled SOD1 was produced to be used as a spike material required for species-specific IDMS. Finally, SOD1 was quantified in human erythrocytes using both double and triple IDMS and a complete uncertainty budget for both approaches was estimated according to the Guide to the Expression of Uncertainty in Measurement (GUM). A calculated mass fraction of SOD1 with its associated expanded uncertainty of (63.94 ± 0.93) μg g −1 ( n = 30) for double and (64.02 ± 0.96) μg g −1 ( n = 30) for triple IDMS was obtained.